Unified Standards of the Eurasian Economic Union for Fruit and Vegetable Products as a Means of Integrated Trade in the Global Economic Environment - Moskovenko Nadezhda V.; Tikhonov Sergei L.; Tikhonova Natalia V.; Muratov Askar A. (Техника и технология пищевых производств)
Introduction. A unified system of normative and technical regulation can facilitate export of fruit and vegetables. The research objective was to develop a draft of unified standards for marketing regulation and quality control of fruit and vegetable products that participate in foreign trade in the Eurasian Economic Union (EAEU). Study objects and methods. The study featured draft standards for quality of prepared and packaged food products, classification, size, labeling, packaging, safety indicators, etc. The research also included development programs of interstate standards for technical regulations and objects of technical regulation, i.e. fresh fruit and vegetables. Research methods involved comparison, analysis, synthesis, peer review, comprehensive standardization, and system analysis. Results and its discussion. The present article provides an analytical review of the world export of fruit and vegetables by EAEU countries. Export to third countries demonstrated a positive growth trend: the export of vegetables increased by 19.3% and that of fruit – by 3.6%, in comparison with 2018. The paper focuses on the structure of the drafts, their main tasks and advantages. It gives a detailed description of drafts that regulate pre-export standards (quality, commodity procedures, packaging, etc.), as well as post-export requirements. The authors developed standards that specify maturity, calibration, labeling, hygienic requirements, contaminants, etc. The draft standards may help to regulate the sale and control of the commercial quality of fresh fruit and vegetables, including organic products. Conclusion. The new international standards for fresh fruit and vegetables, including organic products, will reduce procedural and documentary barriers between the EAEU and the world market, thus increasing the volume of foreign trade in fruit and vegetables.